Relative Importance of Salt Marshes as Range Resources in The North Western Mediterranean Coast of Egypt - El-Morsy*, M.H.M. (Journal of Phytology, 2010)
The present investigation was carried out to study the relative importance of range plants in Abu Lahu Bahary and Sidi Abd Al-Rahman salt marshes, on the Northwestern Coast of Egypt from spring 2005 to autumn 2006. Fifteen plant species belonging to 7 families were found (15 in the first salt marshes and 14 in the second one). Thirteen species were perennials and two species were annuals. According to palatability five plant species (33.3%) were palatable and ten plant species (66.7%) were unpalatable. Fresh and dry foliage yield, species density, frequency, coverage and the importance value (IV) as well as their relative values were determined in both sites.Ã‚Â The highest value of studied parameters was recorded in Abu Lahu Bahary (West Site) in spring seasons during both years (2005 and 2006). Meanwhile, the lowest values of all these traits were recorded in Sidi Abd Al-Rhman (East Site) during autumn seasons. No significant difference was found between both years. Significant interaction was noticed among the studied factors i.e. year, location and season in both salt marshes. The highest figure of importance value (IV) was contributed by Halocnemum strobilaceum (33.75) followed by Arthrocnemum glaucum (33.13) and Anabasis articulata (31.58) in the first sites.Ã‚Â In the second location (East Site salt marshes) the highest values were found in Halocnemum strobilaceum (39.77) followed by Anabasis articulate (36.68) and SalicorniaÃ‚Â fruticosa (34.35).Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â